2019
DOI: 10.1097/corr.0000000000000955
|View full text |Cite
|
Sign up to set email alerts
|

What is the Likelihood That Tumor Endoprostheses Will Experience a Second Complication After First Revision in Patients With Primary Malignant Bone Tumors And What Are Potential Risk Factors?

Abstract: Background Endoprosthetic reconstruction of massive bone defects has become the reconstruction method of choice after limb-sparing resection of primary malignant tumors of the long bones. Given the improved survival rates of patients with extremity bone sarcomas, an increasing number of patients survive but have prosthetic complications over time. Several studies have reported on the outcome of first endoprosthetic complications. However, no comprehensive data, to our knowledge, are available on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 35 publications
2
55
1
Order By: Relevance
“…Patients who undergo extremity sarcoma resection and megaprosthetic reconstruction are at a high risk for prosthetic failure and subsequent revisions [ 3 , 18 , 19 ]. Orthopaedic oncologists are therefore required to evaluate possible risk factors for failure and, ideally, identify areas of optimization potential.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Patients who undergo extremity sarcoma resection and megaprosthetic reconstruction are at a high risk for prosthetic failure and subsequent revisions [ 3 , 18 , 19 ]. Orthopaedic oncologists are therefore required to evaluate possible risk factors for failure and, ideally, identify areas of optimization potential.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the study spans a fairly long period of time, during which surgical technique, implant design and adjuvant treatments have evolved to a certain degree and which is a cause for some inhomogeneity in our cohort. On the other hand, this allowed us to achieve a long follow-up period, and we have previously demonstrated that implant survivorship in our cohort did not differ for patients treated at different points during the study period [ 3 ]. Furthermore, we attempted to partially offset the impact of such an inhomogeneity by only including patients treated at a single institution and with a single modular megaprosthetic system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations